VOCABULARY IMPROVEMENT THROUGH SONG MEDIA TO CREAT A NARRATIVE STORY FOR CLASS 9 STUDENTS - Muhammad Rifai (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2021)
This study aims to determine how song media in English learning can improve narrative writing outcomes in 9H grade students of SMP Negeri 1 Batu in the odd semester of the 2018 – 2019 school year. The method used in this study is Class Room Action Research. which consists of 2 cycles, using a scientific approach, which consists of observing, asking questions, collecting data, associating and communicating. The conclusion is that learning English using song media in increasing students' vocabulary can be used as an alternative media to motivate students, especially in writing narrative stories.